COMPARATIVE PERSPECTIVES ON TEACHING UZBEK AND ENGLISH LANGUAGES. - Abdurazzaqova Mehriniso Azimjon qizi; Qudratova Azizaxon Tulqin qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This paper explores the similarities and differences in the pedagogy of English and Uzbek languages by analyzing their status, linguistic features, instructional resources, and teaching approaches. English is taught globally as a second or foreign language, supported by extensive educational materials and standardized assessments. Uzbek, primarily spoken in Central Asia, is taught as a native or heritage language and increasingly as a foreign language. The article compares their instructional methodologies, learner motivations, and curriculum challenges. It concludes that while both languages share core objectives such as communicative competence, their unique structures and socio-cultural contexts require tailored teaching strategies.